THE POSITION OF TOURIST AND AGROTOURIST GUESTHOUSES IN ROMANIA'S ACCOMMODATION STRUCTURES - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the position of the tourist and agrotourist guest houses in Romania's accommodation structures in the period 2007-2015. The tourist offer in terms of the number of tourist and agro-tourist guesthouses and of the number of places/beds in this type of accommodation units has continuously increased because of the demand growth in terms of the number of tourist arrivals and overnight stays. This is a consequence of the visitors need to apply for a new alternative to the classical tourism, and of the rural population to diversify the activities in order to get more incomes per family. Tourist and agritourist pensions offer a pleasant stay to their visitors at lower prices compared to hotels. The holidays planning in the middle of the year and the trend to shorten the length of the stay have led to a decline of the net use of the accommodation indices in touristic and agrotouristic pensions, in tourism in general. The results showed that tourist and agrotourist pensions play a more and more important role in Romania's tourism and their services are more attractive in comparison to other sorts of accommodation units. Important efforts must be done by the local population and communities, local authorities, entrepreneurs, local and national administrations and tourism associations in order to promote and support the growth of touristic activities in tourist and agrotourist guesthouses.